KEEFEKTIFAN PERMAINAN TIC TAC TOE PADA MATERI SISTEM EKSKRESI MANUSIA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK - Mailaturrobiatis Sa’diyah; Laily Rosdiana; Aris Rudi Purnomo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
The research aimed to describes the effectivity of Tic Tac Toe game based on in terms of increasing students' understanding towards of concepts human excretory system. The type of research used was Research and Development (R & D) design within which it had been limited to pilot project. The pilot project involved 30 students at SMP Negeri 40 Surabaya level of grade 8th. The instruments used in this research is conceptual understanding test sheets. The understanding of test results was analyzed using the N-gain formula. The results of the effectiveness study of the developed Tic Tac Toe game can be reviewed from the results of the students' pretest and posttest analysis. Analysis of students' pretest and posttest results showed that the acquisition of an N-gain score of 0.71 with high criteria. It can be concluded that the Tic Tac Toe game developed is very suitable to be used as a learning medium and is able to increase students' understanding of concepts.